FARMYARD MANURE EFFECTS ON CARBON SEQUESTRATION POTENTIAL AND SOIL TOTAL NITROGEN IN FODDER MAIZE (Zea mays L.) CROP FIELD OF INDIA - B. Rajesh Kumar; Thanga. Thamil Vanan; T. Sivakumar; K.N. Selvakumar; V.M. Sankaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A field experiment was conducted to assess the influence of inorganic fertilizer and the combined effect of farmyard manure (organic) with inorganic fertilizer on soil organic carbon (SOC), carbon sequestration potential (CSP) and soil total nitrogen (STN) in Fodder Maize (Zea mays L.) crop field in North Eastern and Western Zones of Tamil Nadu, India during summer season of 2012. In Western zone two districts viz., Coimbatore and Erode districts and in North Eastern Zone Tiruvannamalai and Vellore districts were selected for the field experiments. From each district, two villages were randomly selected for field experiments totaling to eight experimental sites for the study. The SOC on 30th day of the experimental period varied from 0.28% to 0.44% for treatment 1 (T1) and 0.30% to 0.49% for treatment 2 (T2) in the experimental zones. The SOC on 60th day varied from 0.36% to 0.53% for T1 and 0.40% to 0.58% for T2. Carbon sequestration potential in the soil for the fodder maize crop varied from 1.28 to 2.27 t/ha on 60th day of the trial period. Soil total nitrogen for fodder maize crop on 30th day varied between 181.67 to 207.33 kg/acre and from 190.50 to 218.17 kg/acre for treatment 1 and 2 in the study zones. On the other hand, on 60th day soil total nitrogen varied from 165.50 to 193.17 kg/acre for treatment 1 and 178.67 to 206.33 kg/acre for treatment 2. The results recommended that integrated use of farm yard manure could be a viable option to sequester carbon than inorganic fertilizer alone which has a definite impact on carbon mitigation.